2023
DOI: 10.3390/designs7020034
|View full text |Cite
|
Sign up to set email alerts
|

Open-Source Vertical Swinging Wood-Based Solar Photovoltaic Racking Systems

Abstract: Vertical bifacial solar photovoltaic (PV) racking systems offer the opportunity for large-scale agrivoltaics to be employed at farms producing field crops with conventional farming equipment. Unfortunately, commercial proprietary vertical racks cost more than all types of conventional PV farm racking solutions. To overcome these cost barriers, this study reports on the development of a new wood-based PV racking design. The open-source design consists of a hinge mechanism, which reduces mechanical loading and e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 73 publications
0
6
0
Order By: Relevance
“…For wheat farmland (e.g. Figure 5), a vertical 2700 W PV mini-array with a width of 4.8 m [108] was used for vertical PV simulations, while a 15,000 W single-axis tracking system with a width of 23 m and depth of 4 m [109] was used as the second system type for PV simulations. To calculate the number of arrays in a single row, the length of one side of the land was divided by the width of the array.…”
Section: Methodsmentioning
confidence: 99%
“…For wheat farmland (e.g. Figure 5), a vertical 2700 W PV mini-array with a width of 4.8 m [108] was used for vertical PV simulations, while a 15,000 W single-axis tracking system with a width of 23 m and depth of 4 m [109] was used as the second system type for PV simulations. To calculate the number of arrays in a single row, the length of one side of the land was divided by the width of the array.…”
Section: Methodsmentioning
confidence: 99%
“…Aluminum, one of the most commonly used construction materials for PV racking structures, has more than 5 times embodied CO 2 e/kg of wood [26], giving wood a distinctive edge. Wood has already been shown to be a cost-effective racking material for fixed tilt [20], variable tilt [27], vertical PV [28] and awning designs [86]. Previous work has shown that the economics of wood vs aluminum racks varies widely by geography [87], but it is superior in most of North America.…”
Section: Selection Of Material: Woodmentioning
confidence: 99%
“…Responsibly-sourced wood is considered sustainable [25], and it has a negative embodied energy when compared with other PV racking materials [20,26]. Several low-cost open-source wood racks have been designed previously for fixed-tilt [20], variable-tilt [27] and vertically-mounted PV systems [28]. No open-source wood racks have been developed for trellis-based crops despite the fact that trellises are often constructed with wood [29].…”
Section: Introductionmentioning
confidence: 99%
“…One approach to reducing costs of small-scale PV systems is to use do-it-yourself (DIY) development of open source technologies [35]. This approach is well developed and there are open source hardware designs for the distributed production of PV racking of the following types of systems: (1) low-tilt angle PV racks for mobile arrays [36], (2) steel cable-based cross X-wire PV racking systems for flat commercial rooftops [37] and groundmounted near the equator [38], (3) tensegrity-based solar PV racking [39], (4) after-market adaptions of conventional modules to allow for building-integrated PV (BIPV) [40], (5) fixedtilt ground-mounted wood-based racks [41], (6) variable-tilt wood-based PV racks [42,43], (7) vertically mounted (sign-based) wood PV racks [44], (8) fence-based PVs for agrivoltaics on existing farm fencing [45], (9) aftermarket adaptation to make floatovoltaics (FPV) [46], (10) trellis-based agrivoltaics wood-based PV racks [47], (11) cable and pipe-based mobile photovoltaic racking [48], (12) cable based variable tilt racks [49], and (13) earth and shotcrete-based racking [50]. There are also many community-developed racking systems made from wood.…”
Section: Introductionmentioning
confidence: 99%